IMPLEMENTATION OF NON CONVICTION BASED ASSETS AGAINST MONEY LAUNDERING AND MONEY CHANGING CRIMES IN INDONESIA - Insan Pribadi (State Institute of Islamic Studies (IAIN) Salatiga, 2021)
Money Laundry is an extraordinary crime with the act of hiding or disguising the money or assets obtained from the proceeds of a crime. Money Laundry is closely related to other criminals, including corruption as a predicate crime. Due to the development of criminal acts, a new breakthrough emerge which was echoed in The United Nations Convention Against Corruption in 2003 named Non-Conviction Based Asset Forfeiture, which is a legal mechanism that allows the owned assets that have been taken by criminals and is possible to be confiscated again.